1995
DOI: 10.1136/adc.72.4.290
|View full text |Cite
|
Sign up to set email alerts
|

Outcome in children from cryopreserved embryos.

Abstract: A cohort of 91 children from cryopreserved embryos and 83 control children who were conceived normally had their development assessed using the Griffiths's scales of mental development. The controls (81 singletons and two twins) of a similar age, sex, and social class were selected from siblings, cousins, and peers of the cryopreserved embryo group (68 singleton, 20 twins, and three triplets). Children from cryopreserved embryos had a lower mean birth weight and mean gestational age and a higher proportion wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
18
0
2

Year Published

1998
1998
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(25 citation statements)
references
References 12 publications
5
18
0
2
Order By: Relevance
“…Some studies showed the same findings [6,10,18]. Although Wada et al reported major malformation in cryopreserved group was significantly lower than in standard IVF group [2], a recent study showed, a significantly higher major malformation rate in FET group compared with fresh ET group.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Some studies showed the same findings [6,10,18]. Although Wada et al reported major malformation in cryopreserved group was significantly lower than in standard IVF group [2], a recent study showed, a significantly higher major malformation rate in FET group compared with fresh ET group.…”
Section: Discussionsupporting
confidence: 46%
“…Many studies have shown that major malformation rates in children born after FET are comparable with those in children born after fresh ET and those in children after spontaneous conception [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Measurements ~f head circumference and length, both at birth and at two years of age, were lower than normal. These data are consensual, reflecting both the results of studies that used control groups and surveys of IVFJET national registries (e.g., Andrews et al, 1993;Australian In-Vitro Fertilisation Collaborative Group, 1985;Beral & Doyle, 1990;Brandes et al, 1992;Fridler, Mashiach, & Laufer, 1992;Lancaster, 1985;Leiblum, Kemmann, Colburn, Pasquale, & Delisi, 1987;Medical Research International Society, 1992;National Perinatal Statistics Unit, 1987;Nygren, Bergh, Nylund, & Wramsby, 1991;Raoul-Duval, Bertrand-Servais, Letur-Konirsch, & Frydman, 1994;Rizk et al, 1991;Rufat, Olivennes, De Mouzon, Dehan, & Frydman, 1994;Steptoe, Edwards, & Walters, 1986;Sutcliffe et al, 1995;Tan, Doyle, & Campbell, 1992;Wennerholm, Janshon, Wennergren, & Kjellmer, 199 1;Yeh et al, 1990).…”
mentioning
confidence: 96%
“…Few studies investigating short-and long-term outcomes in children born after cryopreservation of embryos (Cryo children) have included an appropriate control group (7)(8)(9)(10)(11)(12)(13)(14). The early studies were small retrospective hospital-based cohort studies providing reassuring data in terms of birth weight (BW) and gestational age in Cryo children.…”
mentioning
confidence: 98%